2008
DOI: 10.1163/156855508x363870
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cardanol-Based Epoxy Systems

Abstract: The use of cardanol, a renewable natural resource, in place of a phenol or diphenol, in the synthesis of two different epoxy systems has been studied in this work. Cardanol, prepared by the distillation of cashew nut shell liquid (CNSL), was epoxidised using epichlorohydrin in presence of caustic soda catalyst at different reaction intervals and the products were characterized by spectroscopy, gel-permeation chromatography and by determining the epoxide equivalent. The epoxide equivalent increased sharply with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…12,13 Epoxy resins derived from cardanol, a by-product of the cashew nut industry, have also received attention from both academic and industrial research groups. [14][15][16][17][18] Relative to DGEBA, cured cardanol-based epoxy resins possess a low modulus and glass transition temperature. 16 However, cross-linked materials from cardanol epoxy resins retain good flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Epoxy resins derived from cardanol, a by-product of the cashew nut industry, have also received attention from both academic and industrial research groups. [14][15][16][17][18] Relative to DGEBA, cured cardanol-based epoxy resins possess a low modulus and glass transition temperature. 16 However, cross-linked materials from cardanol epoxy resins retain good flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that combining DGEBA with the glycidyl ether of cardanol increased cured thermoset flexibility but had little to no effect in changing the material's impact strength. 17 The Cardolite Corporation sells a commercial flexible epoxy resin under the trade name Cardolite NC-514 (NC-514). Its thermomechanical and chemical properties are published.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxidation of cardanol was performed based on the previously reported literature. [19,20,26] Equimolar amount of cardanol and epichlorohydrin were introduced in to a three necked round bottom flask equipped with a reflux condenser, mechanical stirrer, thermometer and dropping funnel. The mixture was heated slowly over an oil bath until the content in flask starts refluxing.…”
Section: Synthesis Of Epoxidized Cardanol (Epc)mentioning
confidence: 99%
“…Sharp intense peak of methylene C─H stretching vibration was noticed at 2932, 2853 cm −1. [6,[19][20][21] Peaks at 1585 and 1445 cm −1 recommends to the C═C stretching vibration of benzene ring [30] and the explicit existence of small peaks near 904, 953, and 997 cm −1 showed the presence of adjacent hydrogen atom and substitution in benzene ring. [23] 1267 and 1145 cm −1 peaks correspond to asymmetric C─O stretching vibration of C─O─C linkage and to the C─OH vibration.…”
Section: The Basic Parameters Of the Synthesized Resinmentioning
confidence: 99%
See 1 more Smart Citation